Prosperity gospel and the culture of greed in post-colonial Africa: Constructing an alternative African Christian Theology of Ubuntu - Mashau, Thinandavha D.; Kgatle, Mookgo S. (Verbum et Ecclesia, 2019)
Christianity in post-colonial Africa is highly influenced and shaped by the prosperity message. The popular and materialistic gospel is sweeping across the continent like a gale-force wind, which is irresistible. Previous studies on prosperity gospel have indeed defined the concept as a global phenomenon and in an African context. This study is an interdisciplinary reflection on prosperity gospel and the culture of greed in post-colonial Africa. The study proposes the African Christian Theology of Ubuntu as an alternative to prosperity gospel. Ubuntu is prescribed here as an antidote to the culture of greed in prosperity gospel because it is a theology of life, care, solidarity, economic justice, hope and accompaniment.
free